Allogeneic hematopoietic cell transplant overcomes the poor prognostic value of CDKN2 deletion in adult B-lineage acute lymphoblastic leukemia. (10th July 2021) - Ling, Yiwen; Xu, Na; Zhao, Ke; Han, Lijie; Zhang, Qing; Fan, Zhiping; Huang, Fen; Chen, Zhuowen; Xuan, Li; Liu, Hui; Xu, Jun; Chen, Xiaoxia; et al.
Abstract: Emerging evidence suggested that CDKN2 deletion was a poor prognosis predictor in adult B-lineage acute lymphoblastic leukemia (B-ALL). Here, we investigated the effect of allogeneic hematopoietic cell transplant (allo-HCT) on adult B-ALL with CDKN2 deletion. The patients with adult B-ALL underwent more than two courses of chemotherapy were enrolled in the multicenter retrospective study. Relapse and survival were analyzed. A total of 1336 adult B-ALL, including 295 patients with CDKN2 deletion and 1041 wild-type (WT), from five institutes were enrolled. The complete remission (CR) rates were 86.8% and 91.1% (P = 0.229) after two cycles of chemotherapy in patients with CDKN2 deletion and WT, respectively. The 5-year cumulative relapse post-CR were 56% (95% CI, 52–68) and 43% (95% CI, 40–51) (P < 0.001), 5-year disease-free survival (DFS) were 30% (95% CI, 24–36) and 41% (95% CI, 39–46) (P < 0.001), and 5-year overall survival (OS) were 35% (95% CI, 28–39) and 47% (95% CI, 44–49) (P < 0.001) in the two groups, respectively. Subgroup analysis revealed that the 5-year relapse were 89.3% (95% CI, 83.0–96.5) and 68.4% (95% CI, 60.2–72.5) (P < 0.001), 5-year DFS were 4.9% (95% CI, 1.8–10.4) and 22.7% (95% CI, 18.0–27.7) (P < 0.001), and 5-year OS were 6.9% (95% CI, 3.1–12.9) and 23.4% (95% CI, 18.7–28.6) (P < 0.001) in CDKN2 deletion and WT groups undergoing chemotherapy alone, respectively, while there were not different in terms of 5-year relapse (38.1% vs 34.3%, P = 0.211), DFS (48.4% vs 52.2%, P = 0.325) and OS (54.5% vs 56.3%, P = 0.483) between those with CDKN2 deletion and WT undergoing allo-HCT. Multivariate analysis showed that CDKN2 deletion and high-risk stratification both were the risk factors for relapse, DFS and OS, while allo-HCT was a protective factor. CDKN2 deletion might be a poor prognostic predictor of adult B-ALL. Adult B-ALL with CDKN2 deletion might benefit from allo-HCT. Highlights: Emerging reports draw the adverse prognostic value of CDKN2 deletion in acute lymphoblastic leukemia (ALL), the role of allogeneic hematopoietic cell transplant (allo-HCT) on ALL with CDKN2 deletion is still under debate. Five medical centers' data showed that adult B-ALL patients with CDKN2 deletion might benefit from allo-HCT. The adult B-ALL patients with CDKN2 deletion might benefit from allo-HCT.